Environmental filtering drives the establishment of the distinctive rhizosphere, bulk, and root nodule bacterial communities of Sophora davidii in hilly and gully regions of the Loess Plateau of China - Jing, Li; Jia-min, Ai; Xiao-dong, Liu; Ying-ying, Jiang; Chao-chao, Zheng; Rui-hua, Zhao; Zhen-shan, Deng (Frontiers in Microbiology, 2022)
In addition to the rhizobia, other non-rhizobial endophytes (NREs) have been simultaneously isolated from the root nodules. The existence of NREs in leguminous root nodules is a universal phenomenon, and they have the potential to enhance legume survival, especially under conditions of environmental stress. However, the diversity and biogeographic patterns of microbial communities inhabiting root nodules are not well studied or understood. Here, we explored and characterized the diversity of NRE bacteria by using 16S rRNA gene high-throughput amplicon sequencing. Additionally, we compared the biogeography and co-occurrence patterns in review of the bacterial microbiota inhabiting the rhizosphere, the bulk soil and the root nodule bacterial communities associated with Sophora davidii, a native N-fixing wild leguminous shrub in hilly and gully regions of the Loess Plateau of China. The results showed the presence of a large diversity of bacteria belonging to 81 phyla, 154 classes, 333 orders, 463 families, and 732 genera inside the nodules. Proteobacteria were dominant in the nodule and rhizosphere soil samples, and Actinomycetes were dominant in the bulk soil samples. Mesorhizobium was the dominant genus in the nodules, accounting for between 60.15 and 83.74% of the bacteria. The microbial community composition of the NRE in the root nodules differed from that in the rhizosphere soil and the bulk soil of S. davidii. Moreover, we found that the biogeographic patterns and assembly process of the rhizobia and non-rhizobia communities differed in the root nodule, the rhizosphere soil and the bulk soil. Furthermore, the correlation analysis between the soil’s physical and chemical properties and the bacteria showed that available phosphorus was the predominant factor affecting the bacterial diversity within the rhizosphere soil. Finally, our results revealed that the microbial network diagram of co-occurrence patterns showed more complexes in the soil than in the root nodules. This indicates that only specific microorganisms could colonize and thrive in the rhizosphere through the selection and filtering effects of roots. In conclusion, there are significant differences in bacterial community composition in the nodules, rhizosphere and bulk soil in the hilly and gully region of the Loess Plateau, which is the result of environmental filtration. Our study improves the understanding of the biogeographic patterns and diversity of bacterial microbiota inhabiting root nodules and can help quantify and define the root nodule assemblage process of S. davidii.